The anti-diabetic and insulin sensitizing potential of a watery extract of Agathosma tested in rat models of type 1 and type 2 diabetes - Jansen, Vereneque (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.